2018
DOI: 10.1039/c8nr06868b
|View full text |Cite
|
Sign up to set email alerts
|

Computationally-inspired discovery of an unsymmetrical porous organic cage

Abstract: Computationally inspired and rationalised discovery of a completely unsymmetrical organic cage, which was both porous and highly soluble.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 48 publications
0
53
0
Order By: Relevance
“…[38][39][40][41] Ar ecent study showed that low-symmetry cages can be formed using al ower-symmetry aldehyde precursor,b ut the presence of multiple structural isomers precluded the unambiguous characterisation of the cage products. [42] We sought to avoid these problems by designing an alternative single-step route to low-symmetry imine-based cages.W eused mixtures of multiple aldehyde precursors with different geometries to investigate their self-sorting behaviour,s creening for combinations that led to the selective formation of low-symmetry cages.…”
Section: Introductionmentioning
confidence: 99%
“…[38][39][40][41] Ar ecent study showed that low-symmetry cages can be formed using al ower-symmetry aldehyde precursor,b ut the presence of multiple structural isomers precluded the unambiguous characterisation of the cage products. [42] We sought to avoid these problems by designing an alternative single-step route to low-symmetry imine-based cages.W eused mixtures of multiple aldehyde precursors with different geometries to investigate their self-sorting behaviour,s creening for combinations that led to the selective formation of low-symmetry cages.…”
Section: Introductionmentioning
confidence: 99%
“…This includes the use of flow reactors, [68] microwaves, [69] mechanochemistry including ball-milling [70] and twin-screw extrusion, [71] and automated robotic platforms. [16,39,47,72] The latter, in particular, is useful for high-throughput screening, with the former methods suitable for scale-up.…”
Section: Experimental Toolkitmentioning
confidence: 99%
“…Overall, this high-throughput experimental workflow has been successfully applied to the synthesis of two-component binary organic cages of differing topologies (Figure 3), [39,72] the formation of three-component statistical distributions of vertexdisordered cage mixtures, [73] and multi-component self-sorted structures. [47] Additionally, this workflow could have other techniques incorporated at each stage, and be developed to link with property screening, such as crystal packing, porosity, and solubility (Figure 2a, bottom box).…”
Section: Experimental Toolkitmentioning
confidence: 99%
See 1 more Smart Citation
“…Jelfs and co‐workers have shown that computational modeling could be very helpful from design to a synthesis of unusual cage structures through a self‐selection method . A planar C 2V symmetric trialdehyde can produce nine unique [4+6] isomeric cages upon reaction with cyclohexane diamine.…”
Section: Self‐sorting/self‐selection In Oicsmentioning
confidence: 99%